Fabrication and characterization of novel bone void filler made from hydroxyapatite-rice starch composite - Sittiporn Punyanitya (2018)
© 2018 Trans Tech Publications, Switzerland. The aim of this study is fabricated bone void filler (BVF) made from hydroxyapatite (HA)-rice starch (RS) composite. We provided HA derived from cockle shells and RS derived from Thai rice starch. BVF was prepared by adding the pore former method to mimic the pore structure of bones. The samples were heated at 1250°C for 3 hours. Then, the composites were prepared by dipping and coating surface of the samples with RS gel. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) confirmed that bovine bone and BVF are made of HA phase. Film of RS gel coated on surface of samples indicated that BVF without toxicity and would increased the proliferation of bone cells. Moreover, it was found that BVF after coated RS gel had water absorption value higher than before coated as 25% that exhibited a good capacity of regeneration bone.